Public versus private provision of daycare: an experimental evaluation - Tarja K. Viitanen (Institute for the Study of Labor (IZA), 2007)
This paper provides experimental estimates of the impact of a voucher for private care within the Nordic system of universal provision of public care. The private daycare voucher acted as a significant boost for new daycare entrepreneurs to enter the market thus increasing the overall daycare provision in the municipalities participating in the experiment. In a market that was providing high-quality, low-cost public daycare, a voucher is nevertheless found to have a significant, positive effect for the use of private daycare with zero to negligible effects on the use of public care and labor force participation.
Keywords: 330; Kinderbetreuung; Voucher; Öffentliche Dienstleistung; Privatwirtschaft; Wirkungsanalyse; Arbeitsangebot; Mütter; Finnland; Nordeuropa